2022
DOI: 10.3389/fphar.2022.1057829
|View full text |Cite
|
Sign up to set email alerts
|

The role of p53 in liver fibrosis

Abstract: The tumor suppressor p53 is the central hub of a molecular network, which controls cell proliferation and death, and also plays an important role in the occurrence and development of liver fibrosis. The abundant post-translational processing and modification endow the functional diversity of p53. Considering the relationship between p53 and liver fibrosis, drug intervention targeting p53 or management of p53 regulation might be effective strategies to treat liver fibrosis. Here, we systematically discuss the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Therefore, the alleviating effect of 3HB on CCl 4 -induced liver fibrosis may be achieved through the restoring normal function of mouse hepatocyte mitochondria. P53 is involved and required in the anti-fibrosis process [19]. We found that 3HB also regulated the p53 signaling pathway in the liver of mice with liver fibrosis, and affected the expression of p53-related genes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, the alleviating effect of 3HB on CCl 4 -induced liver fibrosis may be achieved through the restoring normal function of mouse hepatocyte mitochondria. P53 is involved and required in the anti-fibrosis process [19]. We found that 3HB also regulated the p53 signaling pathway in the liver of mice with liver fibrosis, and affected the expression of p53-related genes.…”
Section: Discussionmentioning
confidence: 89%
“…5C). P53 is involved and required in the anti-fibrosis process [19]. A total of 7 reported p53 regulated genes were found out from all differentially expressed genes, and 3HB treatment affected the expression of p53 controlling genes (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…As the liver is a site for the elimination of toxic metabolites, the peroxisome is involved in the biosynthesis of bile acids [ 33 , 34 , 35 ]. The p53 signaling pathway is also associated with liver inflammation, fibrosis, and steatosis, and its effect on the liver changes substantially at different stages of liver injury [ 36 ]. Furthermore, several other pathways listed in Table 3 , such as tight junction and ribosome biogenesis in eukaryotes, are also reported to be associated with liver disease [ 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, our results indicate that SIRT7 deficiency increases the migration capabilities of p53-KD MEFs and alters the expression of genes related to cytoskeleton organization and cell-matrix interactions ( Figures 7D–F ). Both SIRT7 and p53 were previously associated with extracellular matrix remodeling during tissue fibrosis ( Wyman et al, 2017 ; Wu et al, 2020 ; Yu et al, 2022 ), but whether this function may be important in other situations is unknown. Because EMT is an essential process in normal embryonic development and organogenesis, our results suggest that the interplay of SIRT7 and p53 in embryonic cells may be important to sustain tissue morphogenesis.…”
Section: Discussionmentioning
confidence: 99%